2000
DOI: 10.1038/sj.bjp.0703737
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin causes endothelium‐dependent biphasic regulation of vascular tone in the porcine renal interlobar artery

Abstract: 1 Using a method employing front-surface fura-2¯uorometry to measure the cytosolic Ca 2+ concentration, [Ca 2+ ] i , the mechanism of endothelium-dependent regulation of vascular tone by thrombin was studied in porcine renal interlobar arterial strips. 2 At concentrations lower than 3 u ml 71, thrombin evoked only early transient relaxation, while at 3 u ml 71 and higher concentrations, thrombin caused an early relaxation and a subsequent transient contraction. Both thrombin-induced relaxation and contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(51 reference statements)
0
41
0
2
Order By: Relevance
“…Full characterization of this vasoconstrictor response was beyond the scope of this study, but it appears to be endothelium-dependent, since it was not observed when the endothelium was functionally impaired with CHAPS. Previous studies have reported anomalous, endotheliumdependent vasoconstrictor responses in rat aorta (FranchiMicheli et al, 2000) and porcine renal interlobar artery (Derkach et al, 2000). A lower concentration of charybdotoxin (10 nM) had no e ect on perfusion pressure or vasodilatation.…”
Section: British Journal Of Pharmacology Vol 134 (4)mentioning
confidence: 80%
“…Full characterization of this vasoconstrictor response was beyond the scope of this study, but it appears to be endothelium-dependent, since it was not observed when the endothelium was functionally impaired with CHAPS. Previous studies have reported anomalous, endotheliumdependent vasoconstrictor responses in rat aorta (FranchiMicheli et al, 2000) and porcine renal interlobar artery (Derkach et al, 2000). A lower concentration of charybdotoxin (10 nM) had no e ect on perfusion pressure or vasodilatation.…”
Section: British Journal Of Pharmacology Vol 134 (4)mentioning
confidence: 80%
“…The arterial strips without endothelium were prepared as previously described. 24,25 The effects of N-terminal fragments of MYPT1 on [Ca 2ϩ ] i , isometric force, and MLC phosphorylation were examined as previously described. 24 -27 All data were expressed as the meanϮSD.…”
Section: Methodsmentioning
confidence: 99%
“…NO, endothelium-derived hyperpolarizing factor (EDHF) and prostacyclin were determined to contribute to the relaxation (101,107). In the porcine renal artery, thrombin induces a biphasic response consisting of an initial endothelium-dependent relaxation and a subsequent endothelium-dependent contraction, while having no effect in the absence of endothelium (82). Prostaglandin H2 and thromboxane A2 were shown to contribute to the endothelium-dependent contraction (82).…”
Section: Endothelium-dependent Regulation Of Vascular Tone By Thrombimentioning
confidence: 99%